(1→3)-β-D-Glucan Levels Correlate With Neurocognitive Functioning in HIV-Infected Persons on Suppressive Antiretroviral Therapy: A Cohort Study. Issue 11 (March 2016) - Hoenigl, Martin; Oliveira, Michelli Faria de; Pérez-Santiago, Josué; Zhang, Yonglong; Morris, Sheldon; McCutchan, Allen J.; Finkelman, Malcolm; Marcotte, Thomas D.; Ellis, Ronald J.; Gianella, Sara
Abstract : Abstract: Microbial translocation from the gut is associated with immune dysfunction, persistent inflammation, and likely plays a role in the pathogenesis of neurocognitive dysfunction during HIV infection. (1→3)-β-D-Glucan (BDG) is a component of most fungal cell walls and might be a useful indicator of gut mucosal barrier impairment. The objective of this study was to evaluate whether higher blood BDG levels correlate with impaired neurocognitive functioning in a cohort of HIV-infected adults with suppressed levels of HIV RNA in blood plasma. In this cross-sectional cohort study, we measured levels of BDG in blood plasma and cerebrospinal fluid (CSF) supernatant samples in a cohort of adults with acute/early HIV infection, who initiated antiretroviral therapy (ART) during the earliest phase of infection and achieved suppressed levels of HIV RNA in blood plasma (<50 copies/mL) thereafter. We compared BDG with established biomarkers of microbial translocation, immune activation, and cognitive dysfunction (evaluated by global deficit score). We found that higher blood BDG levels were significantly related to higher global deficit scores, reflecting worse neurocognitive performance (Spearman r  = 0.47; P  = 0.042) among HIV-infected adults with suppressed viral loads who initiated ART early in infection. Two CSF samples presented elevated BDG levels. Interestingly, these 2 samples originated from the 2 subjects with the highest global deficit scores of the cohort. BDG may be a promising independent biomarker associated with neurocognitive functioning in virologically suppressed HIV-infected individuals.